Perankingan Dosen Berbasis Aktifitas Forum Moodle Menggunakan Metode Fuzzy Tsukamoto - Putra, I Gede Yogi Prawira; Sukadarmika, Gede; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro, 2023)
The online learning process currently utilizes a Learning Management System, one of which is Moodle. Moodle provides a forum menu where the forum is a digital forum for asking questions and answering and sharing between lecturers and students. Lecturer and student activity can be seen from the forum menu. For this reason, research was conducted on the ranking of lecturer activities in the moodle forum. The ranking determination uses the Fuzzy Tsukamoto decision making system. Fuzzy Tsukamoto has step efficiency in determining rules and processing data that has a taboo range and produces crips output. The processing steps carried out are determining the variables, giving weights, creating a fuzzy set of each variable, then the fuzzification process and creating a rule base and finally, defuzzification, namely the calculation of negligence and output. Based on the rule and the predicate alpha value, the appropriate value is obtained to rank the quality of lecturers based on their activities in the moodle forum. Keywords — database, forum, fuzzy, moodle, tsukamoto